ANTESEDEN VARIABEL KUALITAS AUDIT KECURANGAN LAPORAN KEUANGAN - Ivandi, Ivandi; Sitorus, Tigor (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
This study aims to proves the relationship between independence, competence, individual external auditor's responsibility as antecedent variable with financial fraud audit quality,   where as the number of cases of financial scandals by manipulating financial data that occurs in large companies and involve public accountants to make public accountants must pay attention to audit quality.This research use causality research method with causal relationship between independent variable with dependent variable. The data used are primary data obtained using questionnaires distributed to Public Accounting Firm (KAP) in North Jakarta and Central Jakarta. The population in this study are all auditors who work in Public Accounting Firm (KAP) of North Jakarta and Central Jakarta with Sample Random Sampling technique which produces 46 respondents from 8 KAP in 2018. Data analysis using SPSS 21. Based on the results of research, for the first equation of independence and competence variables have a significant positive effect on individual external auditor's responsibility variable. For the second equation for independence variable have significant positive effect to financial fraud audit quality variable whereas for competence variable and individual responsibility of external auditor does not have significant effect to fraud audit quality variable.